2012
DOI: 10.1039/c2sm25263e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cholesterol on nano-mechanical properties of the living cell plasma membrane

Abstract: In this study, we investigated the effects of membrane cholesterol content on the mechanical properties of cell membranes by using optical tweezers. We pulled membrane tethers from human embryonic kidney cells using single and multi-speed protocols, and obtained time-resolved tether forces. We quantified various mechanical characteristics including the tether equilibrium force, bending modulus, effective membrane viscosity, and plasma membrane-cytoskeleton adhesion energy, and correlated them to the membrane c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 57 publications
11
75
0
Order By: Relevance
“…Histological experiments using a photomicrogram would detect the changes in F-actin in GTPγS-treated OHCs. Indeed, Khatibzadeh recently reported that F-actin depolymerization reduces the effect of cholesterol depletion on membrane mechanics, suggesting the possibility that cortical lattice may directly influence outer hair cell membrane mechanics [22]. The change in cytoskeletal-membrane interactions mechanics with change in cholesterol concentration is consistent with the change in prestin function observed in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Histological experiments using a photomicrogram would detect the changes in F-actin in GTPγS-treated OHCs. Indeed, Khatibzadeh recently reported that F-actin depolymerization reduces the effect of cholesterol depletion on membrane mechanics, suggesting the possibility that cortical lattice may directly influence outer hair cell membrane mechanics [22]. The change in cytoskeletal-membrane interactions mechanics with change in cholesterol concentration is consistent with the change in prestin function observed in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Motivated by the pivotal role of F-actin in the mechanical behavior of filopodia and other cellular protrusions, special focus has been on revealing the presence of F-actin within extracted membrane tubes (1, 13-16). However, apart from a single study (9), fluorescent visualization of the F-actin was achieved by staining and fixation of the cells, and literature contains conflicting results regarding the presence or absence of actin in membrane tubes pulled from living cells (8,11,17).Filopodia in living cells have the ability to rotate and bend by a so-far unknown mechanism (13,(18)(19)(20). For instance, filopodia have been reported to exhibit sharp kinks in neuronal cells (21-23) and macrophages (6).…”
mentioning
confidence: 99%
“…The capacity of CD44 to bind to a ligand can depend on intracellular interactions with 1 Cells contain cytoskeletal networks that not only regulate cell morphology but also define the cellular mechanical properties of the cell and participate in the transduction of signals from various surface receptors to the cell nucleus. 22,[30][31][32] Thus, these results indicate that DTIC disrupts the local linkage of CD44 to the cytoskeleton, which may influence the interactions of the CD44 ligand-receptor.…”
mentioning
confidence: 95%